The sustainability scorecard : how to implement and profit from unexpected solutions - Bhatnagar, Urvashi; Anastas, Paul T., 1962- (Berrett-Koehler Publishers, Inc., 2022)
"For decades, sustainability books have pointed a path to more efficient, effective ways to save resources and money, but they just don't seem to be moving the needle. The problem is the sustainably minded haven't convinced skeptics that powerful economic incentives really exist. Using a unique, practical scorecard understandable to any executive in or outside of operations, this book, once and for all, makes the pragmatic argument for sustainable supply chains crystal clear. In the midst of "green fatigue," many leaders have lost sight of the pure success any business can achieve by focusing on hidden supply costs and toxic inputs. The authors show operations and implementation-focused business leaders how to innovate their supply chains to introduce and scale sustainable solutions. Through repeatable, reliable processes that address operating model design and new key performance indicators to scaling, this book is a practical guide that leaders can rely on to make their existing systems more sustainable and profitable"--